Features of cardiac remodeling in sclerodermic lung lesions - A. N. Kharkova; A. V. Sineglazova (Вестник рентгенологии и радиологии)
Objective: to examine the relationship between structural and functional heart remodeling and sclerodermic lung disease.Material and methods. The study involved 62 women: 21 with systemic sclerosis (SSC) (mean age 49,4±2,1 years) and 41 healthy women (mean age 45±1,7 years) (р=0,127). Examination and treatment of patients with SSC was performed according to the guidelines. Instrumental diagnostics included cardiac US, chest X-ray, pulmonary high-resolution computed tomography.Results. SSC patients, as compared to control group, demonstrated significant increase of end-diastolic left ventricular size, septal thickness, left ventricular mass and mass index. End-diastolic and end-systolic left ventricular size was significantly greater in patients with diffuse pulmonary fibrosis than with basal pulmonary fibrosis.Conclusion. Our data indicate significant changes in the structural and functional parameters of the heart in SSC and their relationship with the progression of pulmonary pathology.